Analysis of pro‐ and anti‐inflammatory cytokine gene variants and serum cytokine levels as prognostic markers in breast cancer. Issue 12 (4th August 2018) - Kaur, Raman Preet; Vasudeva, Kanika; Singla, Heena; Benipal, Raja Paramjeet Singh; Khetarpal, Preeti; Munshi, Anjana
Abstract : The aim of current study was to evaluate the genetic variation in all the genes encoding pro‐ and anti‐inflammatory cytokines in association with breast cancer development in patients from Malwa region of Punjab. The importance of the levels of interleukin (IL)‐17, tumor necrosis factor, interferon γ, IL‐10, IL‐6, IL‐4, and IL‐2 with respect to clinicopathological data, prognosis, and disease‐free survival was also determined in these patients. Two hundred and fifty female breast cancer patients and 250 age‐matched controls were screened for variations in cytokine‐encoding genes using global screening array microchip and PCR‐RFLP. The level of cytokines was estimated in 150 patients and 60 age‐matched controls using BD™ Cytometric Bead Array (CBA) Human Th1/Th2/Th17 cytokine kit by BD Accuri flow cytometer. The difference in cytokine levels was evaluated by Mann–Whitney test. No significant variation in the genes encoding various cytokines was found between patients and controls. Out of the seven cytokines evaluated, the levels of IL‐6 and IL‐17a were found to be significantly high in patients in comparison with controls ( p  = 0.001 and 0.02, respectively). The elevated levels of these cytokines are also associated significantly with poor outcome. We did not find any specific variation in the genes encoding various cytokines between patients and controls. However, there was a significant difference in the serum levels of IL‐6 and IL‐17a between patients and controls, and the elevated levels of these two cytokines associated significantly with poor outcome in breast cancer patients and, therefore, can be used as prognostic markers. Abstract : This study was carried in the Malwa region of Punjab where breast cancer was widely feared, and the levels of pro‐ and anti‐inflammatory cytokines were analysed in female breast cancer patients. There was a significant difference in the serum levels of interleukin (IL)‐6 and IL‐17a between patients and controls, and the elevated levels of these two cytokines associated significantly with poor outcome in breast cancer patients and, therefore, can be used as prognostic markers.